Costing the ex situ conservation of genetic resources: maize and wheat at CIMMYT - Pardey, Philip G.; Koo, Bonwoo; Wright, Brian D.; Van Dusen, M. Eric; Skovmand, Bent; Taba, Suketoshi; International Maize and Wheat Improvement Center (International Food Policy Research Institute, 1999)
Worldwide, the number of genebanks and the amount of seed stored in them has increased substantially over the past few decades. Most attention is focused on the likely benefits from conservation, but conserving germplasm involves costs whose nature and magnitude are largely unknown. In this paper we compile and use a set of cost data for wheat and maize stored in the CIMMYT genebank to address a number of questions. What is the cost of storing an accession of either crop for one more year, or, equivalently what is the benefit in terms of cost savings from eliminating duplicate accessions from the genebank? Relatedly, what is the cost from introducing a new accession into the genebank, given the decision to store it is revisited after one year? Does it make economic sense for CIMMYT to discard accessions that may be available elsewhere? As an extension of this line of inquiry it is possible to value the benefits from either consolidating genebanks or at least networking existing banks to reduce or eliminate duplicate holdings not needed for backup safety purposes. We present estimates of the size and scale economies evident in the CIMMYT operation as a basis for assessing the economics of consolidation. Genebanks represent a commitment to conserve seeds for the very long-run. In this study we report on these long-run costs for the CIMMYT genebank costs that are sensitive to the interest rate used and the protocols for periodically replenishing accessions that are shared with others or regenerating accessions whose viability gradually diminishes with age.